Inhibitory Effect of Aconitine on Colorectal Cancer Malignancy via Inducing Apoptosis and Suppression of Cell Motion - Xuehui Li; Jianglin Hu; Duan Tong; Taotao Yang; Ming Deng (The Turkish Journal of Gastroenterology)
Background/Aims: The incidence of colorectal cancer (CRC) has been increasing in recent years worldwide. Aconitine is a diester diterpenoid alkaloid that exhibits an antitumor role in several cancers. Nevertheless, it remains unclear whether aconitine also has antitumor activity in CRC. This study aims to investigate the effects of aconitine on the malignant behaviors of CRC cells.